THE ANALYSIS OF RELATION BETWEEN SOCIO-CULTURAL-ECONOMIC AND TOURISM DEVELOPMENT LEVELS OF THE PROVINCES IN TURKEY - Ebru Kerimoglu; Hale Ciraci (European Regional Science Association (ERSA), 2005)
It is s common fact that tourism is a leading sector in progress of under-developed and developing regions. Consistent with the policies to ensure tourism variety and spreading tourism activities throught out the country in to the four seasons, efforts to find and develope natural, historical, archeological and cultural resources in different regions of Turkey are continuing. In spite of the various tourism potentials of the cities that are developed in urban scale and socio-economic progress, their tourism development levels are not as required. In this study, the tourism policies followed in Turkey since 1970's and influence of those policies on the investment distrubition and space are investigated and the socio-cultural and socio-economic reasons underlying the failure of Turkey's developed cities to reach the required level in the tourism development are stated. Depending on the time, the touristic development levels and socio-economic development levels of Turkish provinces are designated and the relation between them are evaluated.
Keywords: 330